Business mangement for the personal fitness trainer - Ware, Charles M. (McGraw-Hill, 2013)
Business Management for the Personal Fitness Trainer is a handbook for fitness professionals who have entertained the idea of going out on their own and starting their own business. It serves as an entrepreneurial tool to help fitness professionals expand their knowledge and to develop an understanding of the necessary elements in designing, starting, and managing a small business in the fitness industry. It walks through the fundamentals of small business and notes how these apply to the fitness industry. From choosing an idea for a business and developing a business plan to the legal, financial, and operational considerations of opening and running a business, this book is your guide to building a fitness business.